Caring For The Physical Environment: Perceptions Of Secondary School Students In Botswana - Dinama, Baamphatlha; Kahaka, Makotoka; Botlhaetse, Gofaone; Sebopeng, Naledi; Machibe, Clara; Giddie, Banyana T.; Moring, Anthony (Advances in Social Sciences Research Journal, 2017)
The importance of the environment to human kind cannot be disputed since people exist because of the natural environment therefore the responsibility of taking proper care of it lies with human beings of which young people are a part of. The research findings showed that students understood the importance of positive attitudes towards their environment even though they did little to care for it. Students possessed a high level of awareness of what the environment is and ways of sustaining it as well as the implications of not taking care of it. Participants and especially male ones saw the importance of cleaning their environment even though they were reluctant to engage in taking care of it while girls more than boys tended to be more concerned about both personal and environmental cleanliness. The study showed that an individual who has a positive attitude towards an object tends to act positively towards it, and in this case it is the environment, and contrariwise one whose attitude is negative towards the environment tends to be indifferent to it and may even damage it.